2007
DOI: 10.1007/s10147-007-0669-7
|View full text |Cite
|
Sign up to set email alerts
|

The impact of real-time tissue elasticity imaging (elastography) on the detection of prostate cancer: clinicopathological analysis

Abstract: Real-time elastography in conjunction with B-mode ultrasonography significantly improves the detection of prostate cancer. One of the characteristic findings of elastography is its excellent detection of anterior tumors. The low detection rate of high-grade tumors in this analysis was likely due to the predominance of high-grade tumors in a peripheral location compared to the anterior location of the low-grade tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
70
1
4

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(75 citation statements)
references
References 20 publications
0
70
1
4
Order By: Relevance
“…As regards correlation between RTE and Gleason score, Tsutsumi et al [39] observed that RTE reaches a higher detection rate in tumors with low Gleason scores. In contrast, Sumura et al [43] achieved an elevated detection rate in tumors with high Gleason scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As regards correlation between RTE and Gleason score, Tsutsumi et al [39] observed that RTE reaches a higher detection rate in tumors with low Gleason scores. In contrast, Sumura et al [43] achieved an elevated detection rate in tumors with high Gleason scores.…”
Section: Discussionmentioning
confidence: 99%
“…Cochlin et al [38] examined anatomic specimens using RTE to detect prostate carcinoma reporting a sensitivity of 51% and a specificity of 83% related to the number of patients, and a sensitivity of 31% and a specificity of 82% related to the number of biopsy cores. Tsutsumi et al [39] stated that RTE identified neoplastic lesions in 84% of patients who had carcinoma, concluding that a combination of RTE and Bmode US provides an increased tumor detection rate. In a study carried out by König et al [40], RTE associated with Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary use of strain imaging investigated in the clinical literature is for biopsy guidance. As will be reviewed below, many studies have employed conventional biopsy techniques, and then used strain imaging to identify and target additional regions [1,3,23,24,29,31]. Some studies have acquired elastographic strain imaging data and retrospectively compared suspicious regions with those that were biopsied [5] or with whole-mount histology after the prostate was excised [28].…”
Section: Elastographic Imaging Methods In Prostate Strain Imagingmentioning
confidence: 98%
“…The vast majority of prostate elastography clinical studies have employed strain imaging (i.e., compression elastography) because this method has been commercially available for the past decade [1,3,5,[23][24][25][26][27][28][29]. Strain imaging requires the user to obtain a B-mode image of the prostate, then compress the organ and obtain a second The background has linearly varying displacement throughout depth due to the applied force at the top of the tissue and fixed bottom boundary; thus, the background has constant strain, as represented by the yellow line.…”
Section: Elastographic Imaging Methods In Prostate Strain Imagingmentioning
confidence: 99%